Analysis of Flavonoid content and Toxicity Test of Semambu Rattan Leaf Ethanol Extract (Calamus scipionum lour)with Brine Shirmp Lethality Test (BSLT) method - Legasari, Leni; Rahmadona, Shevira Putri; Yani, Dwi Fitri; Oktasari, Ade (Stannum : Jurnal Sains dan Terapan Kimia, 2025)
Semambu rattan is rattan that grows wild in the forest areas of Indonesia, especially in southern Sumatra, Kalimantan, and Sulawesi. This study aims to determine the % yield, phytochemical tests, levels of flavonoids and cytotoxicity of the ethanol extract of rattan semambu leaves using the BSLT method with Artemia salina leach test larvae. The yield % yield contained 9.36%, the phytochemical test of the ethanol extract of the semambu rattan leaves contained secondary metabolites of flavonoids, alkaloids, tannins, saponins, and steroids. The test results for the levels of flavonoids at a concentration of 1000 ppm obtained a value of 53.307 μg/ml and the toxicity test of the ethanol extract of rattan semambu leaves obtained an LC₅₀ 130.390 ppm which was toxic